2009
DOI: 10.1007/s11605-008-0618-4
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Biliary Drainage in Patients with Obstructive Jaundice: History and Current Status

Abstract: Rationale Preoperative biliary drainage (PBD) has been introduced to improve outcome after surgery in patients suffering from obstructive jaundice due to a potentially resectable proximal or distal bile duct/pancreatic head lesion. In experimental models, PBD is almost exclusively associated with beneficial results: improved liver function and nutritional status; reduction of systemic endotoxemia; cytokine release; and, as a result, an improved immune response. Mortality was significantly reduced in these anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
114
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(120 citation statements)
references
References 77 publications
3
114
0
2
Order By: Relevance
“…This could explain the lower rate of vascular resection and reconstruction in the current study. Among patients with obstructive jaundice, PBD is the best way to reduce the bilirubin level to reverse cholestasis-associated liver dysfunction and impaired hepatic regeneration (23). However, there are no guidelines or indications regarding the level of bilirubin that warrants a patient undergoing PBD.A ROC curve was used in the current study to find the cut-off value for TB to indicate PBD.…”
Section: Discussionmentioning
confidence: 99%
“…This could explain the lower rate of vascular resection and reconstruction in the current study. Among patients with obstructive jaundice, PBD is the best way to reduce the bilirubin level to reverse cholestasis-associated liver dysfunction and impaired hepatic regeneration (23). However, there are no guidelines or indications regarding the level of bilirubin that warrants a patient undergoing PBD.A ROC curve was used in the current study to find the cut-off value for TB to indicate PBD.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of toxic substances, such as BIL and bile salts, impaired liver function, and altered nutritional status due to obstructive jaundice have been characterized as factors for the development of complications, including acute renal failure, cardiovascular depression, hemorrhage from vitamin K deficiency and septicaemia. 14,15 An obstructed biliary tree is likely to be infected and, as a consequence, there will be a higher incidence of severe chronic cholecystitis found at operation, necessitating conversion. 8 In addition, patients with higher BIL were more likely to undergo an emergency operation, and an emergency operation was a risk factor for poor outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Presently, the necessity for preoperative biliary drainage is controversial. In several studies, preoperative biliary drainage reduced morbidity and mortality after surgery for periampullary cancer [23] [24]. However, recent studies showed that the overall complication rate in patients undergoing preoperative biliary drainage was higher than that in patients who proceeded directly to surgery and that the procedure increased the rate of complications [25] [26].…”
Section: Discussionmentioning
confidence: 99%